Satellite-Based Earth Observation Trends and Challenges for Economy and Society (Springer International Publishing, 2018)
The book focuses on the topic of trends and challenges with regards to satellite-based earth observation. Contributors include legal experts in the field and representatives from institutions such as the European Space Agency, the European Space Policy Institute, academia and the private sector.